THE STRUCTURE OF CO(ETA-C5H5)(2)(+) AND NME(4)(+) INTERCALATES OF MNPS3 - AN X-RAY, NEUTRON-DIFFRACTION, AND SOLID-STATE NMR-STUDY - Evans, J; Ohare, D; Clement, R (1995)
This paper reports a series of structural studies on the intercalation compounds of MnPS3, with the aim of trying to understand the source of the magnetic and NLO properties they exhibit. Both neutron and X-ray powder experiments and single crystal studies have been performed on Mn1-xPS3{G}2x(H2O)y for G = Co(η-C5H5)2+ [x = 0.34, y = 0.3] and N(CH3)4+ [x = 0.32, y = 0.9]. These investigations have suggested that the individual host layers of these intercalates contain an ordered arrangement of metal vacancies, giving rise to large superlattices in the ab plane of the crystal; it is this vacancy arrangement which is believed to give rise to the changes observed in the magnetic properties of these systems on intercalation. In the case of the Co(η-C5H5)2+ intercalate, the degenerate ways of layer stacking lead to a considerably disordered overall structure such that the 3-dimensional diffraction of this intercalate can be described by a considerably smaller overall unit cell than the pristine host lattice. These layer shifts also lead to a 3-layer repeat structure and a change in symmetry of the host lattice from CZ/m to R3m. The overall diffraction pattern can then be described by a cell of dimensions a = b = 3.532(3) Å, c = 35.57(2) Å, γ= 120°. 2H solid-state NMR experiments have been used to investigate the orientational preferences and dynamic properties of the cobaltocene guest molecules; these have shown a static arrangement of guest molecules at room temperature lying with their principal molecular axes parallel to the host lattice layers. As the temperature is increased the molecules begin to rotate around their C2 axis. The tetramethylammonium intercalate appears to be considerably more ordered than the cobaltocenium intercalate, suggesting the existence of a guest superlattice in addition to the metal vacancy superlattice. The overall structure is then best explained by a hexagonal metal vacancy lattice of dimension a = 10.6 Å, and a guest lattice of dimensions 18.3 × 6.1 Å. The combination of these two cells leads to an overall hexagonal cell of dimensions a = b = 36.6 Å. This suggests that the overall structure of these materials can only be fully explained by adopting a unit cell with the formula Mn60P72S216{Guest}12.